If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + -4 = 9y + 18 Reorder the terms: -4 + 7y = 9y + 18 Reorder the terms: -4 + 7y = 18 + 9y Solving -4 + 7y = 18 + 9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9y' to each side of the equation. -4 + 7y + -9y = 18 + 9y + -9y Combine like terms: 7y + -9y = -2y -4 + -2y = 18 + 9y + -9y Combine like terms: 9y + -9y = 0 -4 + -2y = 18 + 0 -4 + -2y = 18 Add '4' to each side of the equation. -4 + 4 + -2y = 18 + 4 Combine like terms: -4 + 4 = 0 0 + -2y = 18 + 4 -2y = 18 + 4 Combine like terms: 18 + 4 = 22 -2y = 22 Divide each side by '-2'. y = -11 Simplifying y = -11
| 18(x-3)=-6(x-1)+18 | | 20(k-6)=10(-12k-12) | | -19v+4(v-1)=8(10v+12)-5 | | 2(10m+6)+15=-14+3(1+6m) | | x-6-7=18 | | 14=x+y | | (x^2-2x+4)(x^2+3x+4)=14x^2 | | 1495=x^2(.16x+59) | | -5(3-18a)-20=14(-11+6a)+13a | | (x+8)(x-1)(x-2)=0 | | 56+x=5a | | 6x+6x-4x=-40 | | -6(14p-4)=-900 | | 0.12y+0.05(5000-y)=460 | | 6x+7x-4x=-40 | | -189=-9(r+12) | | 0.80x+0.40(130)=0.40(50) | | -10(12k-13)=-470 | | 2(x+3)+3=9 | | 6+8(-2v+6)=-154 | | 8x-7i=3(3x-7u) | | -3(x+6)-4=56-6x | | -9b+8+7b=3b+13 | | -306=-6(7v-5) | | x*4-10=70 | | -4y+2=-2(3y+8) | | X*5-10=115 | | 4-6x=8-2x | | 5x+84=a | | 12-4x=-18+11x | | 5x-8=12+3x | | [(2t-3)*t]*2=40 |